Microbiomes in the context of developing sustainable intensified aquaculture - Lorgen-Ritchie, Marlene; Uren Webster, Tamsyn; McMurtrie, Jamie; Bass, David; Tyler, Charles R.; Rowley, Andrew; Martin, Samuel A. M. (Frontiers in Microbiology, 2023)
With an ever-growing human population, the need for sustainable production of nutritional food sources has never been greater. Aquaculture is a key industry engaged in active development to increase production in line with this need while remaining sustainable in terms of environmental impact and promoting good welfare and health in farmed species. Microbiomes fundamentally underpin animal health, being a key part of their digestive, metabolic and defence systems, in the latter case protecting against opportunistic pathogens in the environment. The potential to manipulate the microbiome to the advantage of enhancing health, welfare and production is an intriguing prospect that has gained considerable traction in recent years. In this review we first set out what is known about the role of the microbiome in aquaculture production systems across the phylogenetic spectrum of cultured animals, from invertebrates to finfish. With a view to reducing environmental footprint and tightening biological and physical control, investment in ‘closed’ aquaculture systems is on the rise, but little is known about how the microbial systems of these closed systems affect the health of cultured organisms. Through comparisons of the microbiomes and their dynamics across phylogenetically distinct animals and different aquaculture systems, we focus on microbial communities in terms of their functionality in order to identify what features within these microbiomes need to be harnessed for optimising healthy intensified production in support of a sustainable future for aquaculture.